The don’t “do-it-yourself” of education: teaching and learning literature as production of collective knowledge - Clarissa Menezes Jordão (Ilha do Desterro)
There has been some uproar about the canon, what constitutes it and what it constitutes, how it is instituted and its validity in the teaching of literature.1 As important as thoughts about what literature should be taught are discussions on how it could be taught. Techniques on teaching reading and foreign language in general have a lot to tell us, but not enough. When we come to the study of literary texts, textual linguistics, discourse analysis, theories of interpretation, all are found wanting; hermeneutics and reader-response criticism have investigated the production/discovery of meaning, problematised the locus of significance, questioned the limits of interpretation, the roles of the reader, of the author, of culture, history and society in the process of reading comprehension/interpretation. All this has a lot to do with literature, but the teaching of foreign literature and what happens in literature classrooms still lacks careful study.